World War I Australian military images from overseas and within Australia, 1915-1919. (1915)
The collection includes images of the Holsworthy camp in western Sydney which was the largest and longest running internment camp in Australia and operated from 1914 to 1920. At its peak it housed 6000 men, both internees and prisoners of war. Whilst those in the camp were primarily German, including naturalised British subjects and Australians of German descent, a range of other nationalities was represented including Japanese, Italians, and Slavs. The camp grew from a collection of tents to a small town of huts complete with theatres, restaurants and cafes, other small businesses, an orchestra and sporting and educational activities. The most troublesome prisoners were housed in a high security gaol known as Sing Sing which was officially Compound number 2. These images were taken by a Captain S. C. (Stanley Charles) Calderwood who was an officer at the Camp.
The collection also includes images of military personnel stationed in Turkey.
Title devised by cataloguer based on acquisitions documentation and reference sources.
Condition: Faded, yellowing, soiled.
Also available online
Keywords: Australia. -- Army. -- Australian and New Zealand Army Corps -- Photographs; Holsworthy Internment Camp -- Photographs; World War, 1914-1918 -- Concentration camps -- New South Wales -- Holsworthy -- Photographs; World War, 1914-1918 -- Prisoners and prisons, Australian -- Photographs; Prisoners of war -- Germany -- Photographs; Prisoners of war -- Australia -- Photographs; Concentration camps -- New South Wales -- Holsworthy -- Photographs; Detention of persons -- New South Wales -- Holsworthy -- Photographs; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula -- Photographs; Holsworthy (N.S.W.) -- Buildings, structures, etc. -- Photographs; Gallipoli Peninsula (Turkey) -- Photographs